Mapping paradigm shifts in the geography of innovation - Oláh Dániel (Sciendo, 2021)
The study quantifies important theoretical tendencies in the geography of innovation in a historical view based on a novel big-data approach. It shows that the field was “born” only in the nineteen eighties after long periods (i.e. the first half of the 20th century) of analysing economic growth and regional development without endogenising the production process of innovation. The paper presents important shifts in the basic assumptions of models with the increasing use of the terms “economic instability” or “asymmetric information” instead of “economic equilibrium” and “perfect information”. These mean a deviation from traditional neoclassical regional economics, which is reflected in the fact that “geography of innovation” gained the same level of popularity in the 2000s as “industrial geography”. The paper shows that although the decline of the Marshallian term “industrial district” stopped in parallel with the work of Becattini, a new innovation systems theory took over the relative frequency of mention of the industrial district by the turn of the new millennium.